PENGARUH EKSTRAK ETANOL DAUN RAMBUTAN (NAPALEUM LAPPACEUM L.) TERHADAP KADAR LDL DAN HDL PADA TIKUS JANTAN - Susilawati, Elis (Journal of Pharmacopolium, 2018)
The leaves of the rambutan (Napaleum lappaceum l.) is alleged to have activity as antihiperlipidemia. This research aims to know the activity of ethanol extract of antihiperlipidemia leaves on animal model of rambutan induced with foods high in carbohydrates and fat. Research methodology used in modeling animal experiments as much as 30 white rats Wistar strain males aged 2-3 months and weight 150-220 grams are grouped into 6 groups  , namely the Group of negative control positive control group (Group induction), the standar group (simvastatin 0,9 mg/kgBw) and group test of ethanol extract of rambutan leave with a dose of 17,5, 35 and 70 mg/kgBw. All groups except the negative control induced eating high carbs and fats as food every day for 29 days. The comparison test and extract given every day in per-oral 3 hours after animals induced. The observed parameters i.e. LDL and HDL cholesterol levels specified are enzymatic. From the results of the study showed that ethanol extracts of leaves of herbs against LDL levels and can increase HDL levels at 70 mg/dose KgBB has the same activity with the activity checklist 0.9 mg/dose simvastatin KgBB. It can be concluded that ethanol extracts of leaves of herbs have lower levels of activity in the LDL and increase HDL levels is best with a dose of 70 mg/kgBw.